2014
DOI: 10.1093/jpids/piu033
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Use of PPE to Prevent Pertussis Exposures in a Pediatric Primary Care Network

Abstract: Our results identified barriers to PPE use and targets for education to prevent pertussis transmission in ambulatory pediatric settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The literature is inconsistent regarding the effect of age on the use of personal protection: Although older workers were found to use more sun protection, 6 younger health care workers were more likely to use personal protective equipment against pertussis. 7 As in our study, others have found that knowledge about the risk motivates prevention. [12][13][14][15] Therefore, further training, including knowledge about leishmaniasis but also about the different preventive measures, seems to be indicated among soldiers deployed to leishmaniasis-endemic areas.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The literature is inconsistent regarding the effect of age on the use of personal protection: Although older workers were found to use more sun protection, 6 younger health care workers were more likely to use personal protective equipment against pertussis. 7 As in our study, others have found that knowledge about the risk motivates prevention. [12][13][14][15] Therefore, further training, including knowledge about leishmaniasis but also about the different preventive measures, seems to be indicated among soldiers deployed to leishmaniasis-endemic areas.…”
Section: Discussionsupporting
confidence: 68%
“…In other occupational groups, like farmers and health workers, factors such as age, perception, skills, knowledge, and time spent at work have been identified to be predictors of their use. [6][7][8][9] Whether these factors also apply to military personnel is still not known.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of an emerging infection and limited available information, personal experience can influence HCWs' perceptions of risk and behaviours related to protective mask use [38,39]. In contrast, a study undertaken in an outpatient paediatric setting, demonstrated that the use of PPE was not influenced by infectious risk perception [40].…”
Section: Knowledge Education and Skill Factorsmentioning
confidence: 99%